New Folks, New Ideas - Kolawole, Olusegun and Eni-Olorunda, Tolu (Macmillan Nigeria Publishers Limited, 2006)
Chief Atubeka considers himself as the custodian of traditional beliefs and practices.but when he is convinced by AIDS Awareness Campaign team,he and his people begin to develop second thoughts and new ideas to combat the dreaded disease- AIDS.
Keywords: Juvenile Fiction